Identification of Factors Influencing Time and Cost Risks in Highway Construction Projects - Bakri, Anis Sazira; Ab.Razak, Muhammad Aminudin; Abd Shukor, Ani Saifuza (International Journal of Sustainable Construction Engineering and Technology, 2021)
The construction of highway projects involves many types of risks throughout the various stages of its project life cycle. Those risks are especially significant due to their impact on the project performance and objectives, mainly in terms of costs and time. Several factors of projects risk had been determined and well explained in the paper. Major risks involved in highway construction in Malaysia are cost risk, safety risk and time risk. Due to lack of opinion from the contractors regarding the critical factors that influencing the project risks mentioned, this study aims to evaluate the contractor’s perspective towards the important factors of risk particularly the cost and time risks in highway construction in Malaysia. The methodology used in this study is by using quantitative method. Questionnaire survey was developed by taking into consideration the factors influencing the cost risk and time risk that had been explained in the literature. The respondents were chosen by purposive sampling which enables the researcher to collect the data comprehensively. Results from this study confirmed that the construction risks and financial risks are most often occurred in highway projects. This research identifies potential factors influencing both cost and time risks that have a possibility to occur in highway projects in Malaysia from the perspective of contractors. Among the key findings of the factors that highly influenced the cost risks in the highway projects in Malaysia include service relocation, removal and replacement of material, design changes, additional works, environmental issues, and price fluctuation. On the other hand, the main factors influencing time risks which mostly related to time overrun/delay are permit approval, weather condition, low workers’ productivity, slow preparation and drawings approval, design changes and error, and shortage of worker. This study contributes to the current body of knowledge by providing researchers and practitioners with a set of important factors related to time and cost risks that need to be consider in improving the performance of highway projects. It is hoped that this study would help the industry to promote project success of highway projects in Malaysia.